An expert opinion on respiratory delivery of high dose powders for lung infections. (3rd July 2022) - Adhikari, Bishal Raj; Dummer, Jack; Gordon, Keith C.; Das, Shyamal C.
ABSTRACT: Introduction: High dose powder inhalation is evolving as an important approach to to treat lung infections. It is important to its identify applications, consider the factors affecting high dose powder delivery, and assess the effect of high dose drugs in patients. Area covered: Both current and pipeline high dose inhalers and their applications have been summarized. Challenges and opportunities to high dose delivery have been highlighted after reviewing formulation techniques in the context of factors affecting aerosolization, devices, and patient factors. Expert opinion: High dose inhaled delivery of antimicrobials is an innovative way to increase treatment efficacy of respiratory infections, tackle drug resistance, and the scarcity of new antimicrobials. The high dose inhaled technology also has potential for systemic action; however, innovations in formulation strategies and devices are required to realize its full potential. Advances in formulation strategies include the use of excipients or the engineering of particles to decrease the cohesive property of microparticles and their packing density. Similarly, selection of a synergistic drug instead of an excipient can be considered to increase aerosolization and stability. Device development focused on improving dispersion and loading capacity is also important, and modification of existing devices for high dose delivery can also be considered.